Corrosion properties of ceria-based coating electrodeposited from alkaline bath on electrogalvanized steel - Rouabhia, F; Hamlaoui, Y; Meroufel, A; Pedraza, F (Journal of Applied Electrochemistry, 2021)
Long-term protectiveness of zinc coatings remains challenging where conversion surface pre-treatments are suggested such as the promising cerium oxide-based coatings. In the present work, the efect of acetic acid addition and of temperature of the bath on the ceria-based coatings produced by cathodic electrodeposition on electrogalvanized steel are investigated. The electrochemical, surface chemistry, and topographical properties are characterized and their corrosion performance is evalu ated in NaCl solution. The results show that the coatings prepared from equimolar mixture of cerium chloride and acetic acid at pH 8 and room temperature were less cracked, had a smaller grain size, and ofered a three-fold increase of the corrosion resistance when compared with those prepared in cerium chloride solution at pH 6. From X-ray difraction patterns, it seems that the deposits obtained at pH 8 are free from corrosion products. Moreover, the porosity of the coatings obtained at pH 8 increases with increasing the bath temperatures indicating that at high bath temperature the deposits become heterogeneous and do not cover the whole surface of the substrate